Harm reduction and equity of access to care for French prisoners: a review - Michel Laurent; Carrieri M Patrizia; Wodak Alex (BMC, 2008)
Abstract Background Despite France being regarded as a model of efficient harm reduction policy and equity of access to care in the general community, the health of French inmates is a critical issue, as harm reduction measures are either inaccessible or only partially implemented in French prisons. Method Using specific inclusion and exclusion criteria, information was collected and analyzed about HIV, HBV and HCV prevalence, risk practices, mortality, access to harm reduction measures and care for French prison inmates. Results Data about the occurrence of bloodborne diseases, drug use and access to care in prisons remain limited and need urgent updating. Needle exchange programs are not yet available in French prisons and harm reduction interventions and access to OST remain limited or are heterogeneous across prisons. The continuity of care at prison entry and after release remains problematic and should be among the primary public health priorities for French prisoners. Conclusion Preventive and harm reduction measures should be urgently introduced at least as pilot programs. The implementation of such measures, not yet available in French prisons, is not only a human right for prison inmates but can also provide important public health benefits for the general population.